"The influence of organisational culture on performance in the public service" - Rockey, Samantha Jane (My University, 2014)
“The pressure on the public service to perform effectively and efficiently is becoming more important, both in terms of increased fiscal constraints and policy requirements. The purpose of this exploratory study was to show that the organisational culture that exists in the public service, operates as significant barrier to optimum performance One of the main findings of the research indicates that a ‘non-culture’ of performance exists in the public sendee, namely a culture that neither actively encourages nor discourages performance. It was also estabhshed that the subcultures that exist in the public service may hinder performance as a result of a ‘cycle of blame’ and conflict that may exist between the subcultures.”